Flexural and fatigue of a composite leaf spring using finite element analysis. (2020) - Loganathan, T.G.; Vinoth Kumar, K.; Madhu, S.
Abstract: The trend in automobile and aircraft industry is to qualify a better alternative material exhibiting good specific strength, light in weight and highly durable to minimize fuel consumption and increase efficiency. Automobile Leaf spring is the component supports vehicle dynamics, in turn travel comfort by offering required stiffness. In this work, automobile leaf spring is the focus of study in terms of material change from the conventional SAE 5160 steel (Chromium steel) to CFRP (Carbon Reinforced Polymer Composite) to have a considerable strength, associated weight reduction with minimised fuel consumption and increases the performance of the vehicle. The present work provides the results of flexural fatigue life and damage incurred for both the material by FE Analysis. In order to obtain the better results of fatigue life of composite materials, various ply orientations are also considered.